The rhetoric of Abraham's faith in Romans 4 - Tan, Andrew Kim Seng (Department of Religious Studies, 2016)
The situation in the Letter to the Romans is one of dissension between Judean and gentile Christians. This dissension is deep seated because it occurs along the fault lines of Judean ethnic identity. Here, Judean Christians define their ethnic identity in terms of possessing the Mosaic law. Two factors aggravate this dissension. First, ethnic identity resists changes. Second, the audience is situated within the Mediterranean agonistic culture where honour is the most sought after limited good. This moves Judean Christians to use the Mosaic law to gain honour from gentile Christians. From a Judean emic perspective, the Mosaic law gains them righteousness. This righteousness is not only a social marker. More importantly, it is a socio-ethical construct that seeks to gain them honour in the eyes of the significant other, God. Consequently, gentile Christians are considered as inferior by Judean Christians. To alleviate this dissension, Paul uses the rhetoric of Abraham's trust (faith) that takes a two-pronged approach. He first undermines the Mosaic law as a means for Abraham to attain a worldwide fatherhood that makes Judeans Abraham's descendants. Paul next explains how trust in God gains Abraham a worldwide fatherhood so that both Judean and gentile Christians can become descendants of Abraham. In this way, Judean Christians' boast toward gentile Christians, and hence, dissension between these two groups are removed.